Pollination promotes ABA synthesis but not sexual reproduction in the apomictic species Zanthoxylum bungeanum Maxim. (13th January 2021) - Fei, Xitong; Shi, Qianqian; Lei, Yu; Wang, Shujie; Qi, Yichen; Hu, Haichao; Wei, Anzhi
Abstract: Apomixis is a form of reproduction that does not involve the fertilization of female gametes by male gametes but instead involves the production of offspring directly from the female parent. The offspring of apomixis are genetically identical to the female parent and inherit its traits. Therefore, apomixis has great potential for application to agricultural genetic breeding. However, it remains unclear whether apomictic species require pollination, and the impacts of pollination on such species are poorly understood. We investigated the effects of pollination on the apomictic species Zanthoxylum bungeanum Maxim. by analyzing its fertilization process, assembling its transcriptome, and measuring hormone concentrations, fruit setting rate and gene expression levels. Transcriptome sequencing of pollinated and unpollinated fruits resulted in a total of 69, 131 PacBio reads. Of these, 7102 genes were up-regulated and 6491 genes were down-regulated. Analysis of the differentially expressed genes (DEGs) and construction of a weighted gene co-expression network showed that many DEGs were involved in plant hormone signal transduction, suggesting that hormonal signaling during development differs between pollinated and unpollinated fruit. The germination rate of Z. bungeanum pollen in vitro was only 11%, and pollen could not germinate in the embryo sac to complete fertilization. Although pollination did not enable Z. bungeanum to complete the sexual reproduction process, it significantly increased abscisic acid (ABA) concentration and fruit setting rate. Spraying 100 μg l −1 ABA also significantly increased the fruit setting rate. Therefore, ABA appears to be a key factor in the regulation of fruit setting in apomictic Z. bungeanum . Based on these results, we suggest that some male plants be cultivated in Z. bungeanum plantations or exogenous ABA be sprayed to increase the likelihood of pollination and thereby increase the fruit setting rate.